Fluctuating oil palm prices in Uganda: impacts and risks involved - Masiga, M. (2020)
This study was undertaken to explore the experience of oil palm pricing around the world, scrutinise the pricing model adopted in Uganda for its smallholder farmers. The study aimed to identify risks that such pricing formulae present to the value chain, and resultant impacts of pricing mechanisms on smallholders, business and the economy, before making concrete proposals and recommendations on how risks and negative impacts may be overcome.